“Teletrabajo y cuarentena: síndrome de burnout en los estudiantes de administración de empresas de la Universidad Antonio Nariño – Bogotá Sede Sur” (2020)
At present, teleworking has become a necessity for many organizations regarding the quarantine that has been experienced, becoming the most efficient tool in the face of the atypical situation that is being experienced in the world, in such a way that it is useful to be able to deepen in the characteristics and in the repercussions that it brings